Pelaksanaan Pembelajaran Berdiferensiasi Berdasarkan Modelitas Belajar Di Sekolah Dasar - yuni yati; Minsih; Endang Fauziati; Yulia Maftuh Hidayati (Elementary Teacher Education Program, Majalengka University, 2023)
This study aims to apply students' sensory learning styles in creating different content, and the factors that contribute to these learning styles. The research method used is a case study using a qualitative approach. The source of the data in this study were the teachers of Kakuka National Elementary School and the contents of the documents/teaching materials they produced. Observation data was collected using interview guidelines, questionnaires and documentation. In-depth observations were made with teachers at Kakuka National Elementary School. Previously teachers were interviewed to obtain data on students applying sensory learning styles when creating different content and the factors that contributed to this learning. After the interviews, teachers at Kakuka National Elementary School administered and completed the questionnaires. Content documentation produced by the teacher is also carried out to obtain accurate data. Data validity was triangulated using sources and techniques. The results showed that: (1) students' sensory learning styles were implemented in creating different learning content; (2) several factors including internal factors and factors influencing the application of students' sensory learning styles when making different learning materials. Internal factors include the teacher's educational background and teaching practices in the classroom. External factors which include infrastructure and facilities, as well as time.